Re-Evaluation of the Survival Paradox Between Stage IIB/IIC and Stage IIIA Colon Cancer - Li, Hongbo; Fu, Guangshun; Wei, Wei; Huang, Yong; Wang, Zhenguang; Liang, Tao; Tian, Shuyun; Chen, Honggang; Zhang, Wei (Frontiers in Oncology, 2020)
Objective: We conducted this large population-based study to re-evaluate the survival paradox between stage IIB/C and stage IIIA colon cancer based on the newest staging criteria. Methods: Colon cancer patients were recruited from the Surveillance, Epidemiology, and End Results (SEER) database using SEER*Stat software (version 8.3.4). We used Chi-square test to compare categorical variables between patients diagnosed with stage IIB/IIC and stage IIIA colon cancer. Survival probabilities were then assessed using the Kaplan–Meier method. Cox proportional hazards models were used to analyze hazard ratios (HRs) and 95% confidence intervals (CIs) of clinicopathologic characteristics for stage IIB/IIC and stage IIIA colon cancer patients. Results: In the current study, a total of 9227 eligible colon cancer patients were collected from the SEER database between 2010 and 2015. It was found that stage IIIA had 66.4% decreased risk of colon cancer-specific mortality compared with stage IIB (HR = 0.336, 95%CI = 0.286-0.394 for stage IIIA, P < 0.001, using stage IIB as the reference) after the adjustment for other known prognostic covariables. And T1N2a colon cancer had significantly lower 5-year overall survival (OS) rate compared with T2N1 disease (74.7% vs. 57.1%, P = 0.018). Conclusions: Our study confirmed the existence of survival paradox between stage IIB/IIC and stage IIIA colon cancer based on the newest staging criteria. What is more, the subgroup analyses revealed that T1N2a had the least influence on the survival paradox. N2a colon cancer seemed to be a worse prognostic factor than T2 disease, which would give us a better understanding of tumor biology of colon cancer and be conducive to the refinement of individualized treatment regimens in stage III disease.